A REVIEW FOR MEDICAL AND DENTAL PROFESSIONALS CONCERNING THE NEW MONKEY POX WARNING - Dr Simrat Bhullar, Dr Harnoor Singh, Dr Reshma Dodwad, Dr Navpreet Singh, Dr Harnoor Singh Sandhu, Dr Avineet Kaur (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2023)
MPXV, or monkeypox virus, is a member of the Poxviridae family and the Orthopoxvirus genus. Only two different species of wild animals—a rope squirrel in the Democratic Republic of the Congo and a sooty mangabey in Ivory Coast—have had a virus isolated from them. Protection against monkeypox infection after receiving the smallpox vaccine was calculated to be around 85%. Since smallpox was finally eradicated in 1980, widespread vaccination campaigns have tapered down. That opened the door for monkeypox to be considered as a bioterror threat. Keywords : Monkeypox, Diagnosis, Africa, and the United States